Isolation and characterization of infectious Vibrio sinaloensis strainsfrom the Pacific shrimp Litopenaeus vannamei (Decapoda: Penaeidae) - Ma. del Carmen Flores-Miranda; Antonio Luna-González; Ángel I Campa Córdova; Jesús A Fierro-Coronado; Blanca O Partida-Arangure; José Pintado; Héctor A González-Ocampo (Revista de Biología Tropical, 2012)
Infectious diseases especially those caused by bacterial and viral pathogens are serious loss factors in shrimp farming. In this study, bacteria were isolated from the gut and hepatopancreas of stressed shrimps obtained from a commercial farm. The isolates were screened on Thiosulfate citrate bile salt sucrose (TCBS) agar plates for the selection of Vibrio species. Presumptive vibrios were characterized through tests for hemolytic and enzymatic activity, hydrophobicity, growth and molecular identification. Three experimental infections were conducted in order to confirm the pathogenicity of selected bacterial strains VHPC18, VHPC23, VHPC24 and VIC30. In the third experimental challenge the LD50 was obtained, it lasted 10 days with 10 shrimp, weighing 6.9±1.1g, per tank. The treatments in triplicate were: (1) saline solution (control group); (2) 2×10(5)CFU/shrimp; (3) 4×10(5)CFU/shrimp; (4) 2×10(6)CFU/shrimp; (5) 4×10(6)CFU/shrimp, and (6) 8×10(6)CFU/shrimp. In all challenges, water parameters measured during the experimental period remained within optimum ranges. Pathogenicity tests confirmed that the mixture of four vibrio isolates, identified as Vibrio sinaloensis, was virulent for L. vannamei. The LD50 value was 1.178×10(5)CFU/g body weight. V. sinaloensis may act as opportunistic pathogens for cultured L. vannamei. Rev. Biol. Trop. 60 (2): 567-576. Epub 2012 June 01.